The Role of Radiotherapy in Ovarian Serous Carcinoma with Leptomeningeal Metastasis: A Case Report - Ergun, Fatma Humeyra; Erdem, Mehmet Yasin; Cihan, Yasemin Benderli (Archives of Case Reports, 2026)
Ovarian cancer accounts for 4% of all cancers in women and very rarely metastasizes to the leptomeningeal region. Recent advances in systemic treatment options and the resulting increase in survival have led to an increase in central nervous system metastases. Radiotherapy plays a crucial role in the multidisciplinary management of leptomeningeal metastases. This study will discuss a case of serous ovarian carcinoma that presented to our clinic with leptomeningeal metastases two years after surgery and adjuvant chemotherapy, for which we administered palliative radiotherapy.